Tax incentives for private life annuities and the social security reform: Effects on consumption and on adverse selection - Susanne Pech (Johannes Kepler University of Linz, Department of Economics, 2002)
In this paper we analyse several measures which are typically included in a social security reform: a cut in the social security benefits, an increase in the social security tax and tax incentives for the purchase of private life annuities, which have recently become quite popular at the political level. In a two-period model with uncertainty about life-expectancy, it is shown that for a given annuity price tax incentives for life annuities increases consumption expenditures in old-age, while the opposite occurs by a cut in the social security benefits and by an increase of the social security tax. The main result is that a tax incentive for life annuities and a cut in the social security benefits alleviate adverse selection in the private annuity market, while an increase in the social security tax exacerbates adverse selection.
Keywords: D82; D91; G22; H24; H55; 330; annuity market; uncertain lifetime; adverse selection; tax incentives; social security; Sozialreform; Private Rentenversicherung; Steuerbegünstigung; Adverse Selektion; Theorie; Leibrente